The effect of raster orientation on the static and fatigue properties of filament deposited ABS polymer. (July 2019) - Jap, Natalie S.F.; Pearce, Garth M.; Hellier, Alan K.; Russell, Nicholas; Parr, William C.; Walsh, William R.
Graphical abstract: Highlights: Raster orientation of filaments affects fatigue properties of ABS FFF parts. A log-linear S-N curve predicts the fatigue life over a range of stress levels. Raster angle affects static and fatigue strengths (at a fixed life) proportionally. Abstract: Fused Filament Fabrication (FFF) is a cheap, accessible and common Additive Manufacturing (AM) technique. FFF is highly flexible, robust and uses stable and easily transportable precursor materials. Although the static mechanical properties of FFF components are well documented, the dynamic mechanical properties are still not fully established. It was identified that raster orientation was a significant factor in determining tensile strength, and thus could also affect fatigue strength. Dogbone specimens of Acrylonitrile Butadiene Styrene (ABS) were tested under sinusoidal tension-tension fatigue loading at a frequency of 5 Hz, and at 40%, 60%, 80% and 90% of the mean ultimate tensile strength (UTS) of the respective −45°/45° and 0°/90° raster orientations determined from static tensile tests. Sample sizes of 5 were used for each stress level. Statistical analysis of the results showed that the two raster orientations fail at a statistically equivalent number of cycles when fatigued at the same percentage of UTS. However, when tested at the same absolute stress, the −45°/45° raster orientation exhibited a greater number of cycles to failure by as much as 63.5%. A linear fatigue model was derived for each raster orientation based on a single static test which has the potential to simplify component design and testing requirements.